On the Problem of Standardization of the Technique of Normative Legal Acts - A. Yu. Glushakov; A. I. Sobolevskaya (Теоретическая и прикладная юриспруденция)
The active development of public relations, the formation of new areas requiring legislative regulation, leads to the adoption of a large number of normative legal acts. The work is carried out in a short time, the practice of “batch” acceptance of documents is widespread, which reduces the quality of regulatory legal acts. Along with this, the terminological apparatus is growing, which leads to contradictions between acts, gaps in legislation. Issues of legal technique require regulatory and methodological reinforcement. This actualizes the adoption of the Federal Law on Regulatory Acts in the Russian Federation, taking into account the study of the shortcomings that were made in previous bills.